Oxford children's encyclopedia vol. 3: ghosts to monsoon - OUP (Oxford Universty Press Oxford, 1991)
This seven-volume reference work, designed for children age 8 to 13, features an informal text, extensive cross-referencing, diagrams and captions which enhance the text, and separate biography and index volumes which contain much useful information, including articles on 500 famous people.